Homogenization of masonry using a micro-mechanical model : compressive behaviour - Zucchini, Alberto (2006)
Despite considerable experimental and analytical research in the past, modern regulations still adopt very conservative simplified formulas for the compressive strength of masonry. The present paper contributes to the understanding of masonry under compression, using a novel non-linear homogenisation tool that includes the possibility of tensile and compressive progressive damage, both in the unit and mortar. The simplified homogenised model uses an iterative procedure and a few ingenious micro-deformation mechanisms, being able to accurately reproduce complex simulations carried out with non-linear continuum finite element analysis, at a marginal cost of CPU time and with no convergence difficulties.